Swedish - Finnish glossary: mythical figures - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish - Finnish glossary with names of mythic figures. Parts of the glossary previously published in Kieliviesti 2/1993, 3/1999, 4/1999, 2/2000, 1/2002. Contains 607 entries.

Swedish - Finnish glossary with names of mythic figures. Parts of the glossary previously published in Kieliviesti 2/1993, 3/1999, 4/1999, 2/2000, 1/2002. Contains 607 words.

En svensk-sverigefinsk ordlista med namn på sagofigurer. Delar av listan tidigare publicerade i Kieliviesti 2/1993, 3/1999, 4/1999, 2/2000, 1/2002. Ordlistan innehåller 607 uppslagsord.
Svensk-finsk ordlista: sagofigurer
Keywords: Cartoons as Topic; Tecknade serier som ämne; Fantasy; Fantasi; Cartoon; Tecknad serie [Publikationstyp]; word list; ordlista; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur